Napoleon and the Revolution - Jordan, David P., 1939- (Palgrave Macmillan, 2012)
Napoleon was much more than a warlord consumed by vanity and ambition. He was the very spirit of the militant Revolution. Virtually everything he did during the fifteen years of his preponderance was derived from and linked to the French Revolution. Much of his hold over contemporaries was his embodiment of the aspirations as well as the boundless energy of the Revolution. Even his enemies, foreign and domestic, were fascinated by the man and uniformly saw him as 'the Revolution on horseback'. He fought off vengeful reactionary powers long enough for the Revolution to sink deep and permanent roots in France. The Allies who finally defeated Napoleon found it impossible to undo his subversive work - the genii of the Revolution was out of the bottle, and for good. Through his incessant table talk and dictated autobiography he focused the attention of posterity, inculcating his version of himself, events, and their significance.